The Impact of Repeated Reading Technique as A Phonological Practice Tool for Enhancing Pronunciation Clarity in EFL Learners at 11th Graders MA Birrul Walidain NW Rensing - Iswari Maulinda; Ari Prasetyaningrum; Ahmad Yusri; Siti Maysuroh (Universitas Cokroaminoto Palopo, 2025)
Pronunciation clarity is one of the most crucial aspects in mastering English for EFL learners, yet many students still struggle with phoneme articulation, word stress, and intonation. Preliminary observation at MA Birrul Walidain NW Rensing revealed that 11th-grade students frequently mispronounced phonemes such as /θ/ and /ð/, misplaced stress, and produced monotonous intonation, which hindered their intelligibility and confidence. This highlights the urgency of applying an effective and structured phonological training method to improve students’ pronunciation. The present study aimed to examine the impact of the Repeated Reading (RR) technique as a phonological practice tool to enhance pronunciation clarity. This research employed a quantitative approach with a quasi-experimental non-equivalent control group design. The study was conducted at MA Birrul Walidain NW Rensing during the 2025/2026 academic year, involving 26 eleventh-grade students selected randomly into experimental (n=12) and control groups (n=14). Data were collected through pre-test and post-test oral reading tasks, assessed with a pronunciation rubric covering both segmental and suprasegmental features. The instrument was validated by two English teachers, and data were analyzed using SPSS through Shapiro-Wilk test, Levene’s test, Paired Sample t-Test, and Independent Sample t-Test. The results showed that the experimental group’s mean score increased from 9.00 to 12.58 (SD=2.49 to 2.30), with a mean difference of 3.58 (t=10.62, p=0.000). In contrast, the control group only improved from 9.00 to 9.64 (mean difference=0.64, t=1.64, p=0.125). Independent Sample t-Test confirmed a significant difference in post-test scores between groups (mean diff=2.94, t=2.83, p=0.009). These findings indicate that RR significantly enhances pronunciation clarity, particularly in phoneme accuracy, stress placement, intonation, and rhythm. Thus, repeated reading can be considered an effective strategy for EFL pronunciation instruction.